Reconstituting the cytoskeleton - Vale, Ronald; Akhmanova, Anna (Methods in enzymology, 2014)
This new volume of Methods in Enzymology continues the legacy of this premier serial with quality chapters authored by leaders in the field. This volume covers cytoskeletal structure, including such topics as rotational movement of formins studied by fluorescence polarization microscopy, in vitro assembly assays for bacterial actin filaments, and modulators of microtubule plus end growth. Continues the legacy of this premier serial with quality chapters authored by leaders in the field. Covers cytoskeletal structure.